(untitled) (Research, Society and Development, 2020)
Cleidocranial dysplasia (CCD) is a rare syndrome, occurring at a rate of 1:10,000,000 in the form presented in this clinical case. This syndrome occurs due to an autosomal dominant inheritance characterized by changes in skeletal formation and development, as a result of a mutation associated with the RUNX2 gene, the main regulatory gene for osteoblastic differentiation, resulting in manifestations such as hypoplastic or aplastic clavicles, brachycephaly, hypoplasia of the middle third of the face, and delay or non-closure of fontanelles. Specifically, in the intraoral region, atypical dental manifestations occur, such as failure in the exfoliation of the primary dentition, delayed eruption of permanent teeth, and multiple supernumerary teeth. Thus, this study aims to present a case report of a patient with the pathognomonic characteristics of the syndrome in its rarest form, as well as the radiographic, imaging and clinical manifestations that allow its diagnosis and a discussion on the common manifestations in such patients, forms of treatment, and the conduct of treatment according to the specific needs of that case..